2003
DOI: 10.1002/bdra.10132
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of the neural tube defect mouse model bent tail is not sensitive to maternal folinic acid, myo‐inositol, or zinc supplementation

Abstract: Bent tail appears to be a folinic acid-, myo-inositol-, and zinc-insensitive mouse model for NTDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…The percentage found in Bn matings was in accordance with the results of studies at later embryonic stages (Klootwijk et al 2000, and unpublished results), indicating that most of the resorbed embryos already died before ED10. The loss of embryos due to resorption appeared to be linked to the most affected genotypes generating a trend towards under-representation of Bn/Bn and Bn/Y genotypes, consistent with the results of other studies (Carrel et al 2000;Franke et al 2003).…”
Section: Discussionsupporting
confidence: 91%
“…The percentage found in Bn matings was in accordance with the results of studies at later embryonic stages (Klootwijk et al 2000, and unpublished results), indicating that most of the resorbed embryos already died before ED10. The loss of embryos due to resorption appeared to be linked to the most affected genotypes generating a trend towards under-representation of Bn/Bn and Bn/Y genotypes, consistent with the results of other studies (Carrel et al 2000;Franke et al 2003).…”
Section: Discussionsupporting
confidence: 91%
“…For example, cranial NTDs in the curly tail strain appear to largely be a feature of the genetic background as, unlike spina bifida, they are not prevented by transgenic reinstatement of Grhl3 expression (Sudiwala et al, 2016). Spinal closure defects in the Bent tail mouse, carrying an X chromosome deletion that encompasses Zic3 (Franke et al, 2003;Klootwijk et al, 2004), and in Mekk4 knockouts (Chi et al, 2005) were also found to be unresponsive to inositol treatment.…”
Section: Inositol Supplementation In Models Of Ntdsmentioning
confidence: 99%
“…It therefore appears that, depending on genetic, metabolic and environmental context, NTDs may be preventable by either FA, or inositol or both. On the other hand, there are several mutant strains that are non-responsive to either nutrient, including SELH/Bc, the Grhl3 null mutant, mutants for Zic2 and Zic3 [Franke et al, 2003], and MEKK4/ Map3k4-deficient mice [Chi et al, 2005]. …”
Section: Mechanisms and Mouse Models: Nutrient Modulation Of Neural Tmentioning
confidence: 99%
“…A second concern regarding diets is related to the finding that carbohydrate and fat content of the maternal diet [Rosenfeld et al, 2003] and type of polyunsaturated fatty acids [Fountain et al, 2008] can affect the sex ratio in progeny. Because [Marean et al, 2011] Tead2 folic acid resistant [Kaneko et al, 2007] Ski folic acid resistant [Ernest et al, 2006] Grhl3/curly tail inositol-deficiency t folate resistant [Cockroft et al, 1992;Tran et al, 2002] retinoic acid t [Chen et al, 1994] inositol t ] Grhl3 null folic acid and inositol resistant [Ting et al, 2003] Map3k4/MEKK4 folic acid and inositol resistant [Chi et al, 2005] Zic3/bent tail folic acid and inositol resistant [Franke et al, 2003] Increased resorptions and rate of neural tube defects, no effect on survival of particular genotypes. g Inositol supplementation significantly reduced survival of homozygotes and increased, among the survivors, the frequency of individuals with both exencephaly and spina bifida.…”
Section: Selh/bcmentioning
confidence: 99%